Radial growth evolution in a mature stand of Pinus nigra Arn. in the province of Lleida - Meya, D.; González, J. Mª.; Aunóss, A. (Forest Systems, 2001)
An adult stand (mean age = 139 years) of Pinus nigra ssp. salzmannii var. pyrenaica has been studied in the W of the Solsonès district (Lleida province, NE of Spain). Cores from 97 adult trees have been bored and measured, obtaining 13.340 annual rings that have been measured and cross-dated, thus building a growth chronology from 1818 to 1996. The relationships between the measured dendrometrical parameters and the observed growth increments have been analysed, finding generally low correlations. Three growth mean series have been built (average chronology, standarized, and age-based), in order to analyse the stand evolution. A long period of growth slowing and supression that lasted for nearly 80 years was followed by a strong cutting and a growth release reaction, when the mean age of the stand was already of 101 years.